The price vs quantity debate: climate policy and the role of business cycles - Grodecka, A; Kuralbayeva, K (University of Oxford, 2014)
What is the optimal instrument design and choice for a regulator attempting to control emissions by private agents in face of uncertainty arising from business cycles? In applying Weitzman's result [Prices vs. quantities, Review of Economic Studies, 41 (1974), 477-491] to the problem of greenhouse gas emissions, the price-quantity literature has shown that, under uncertainty about abatement costs, price instruments (carbon taxes) are preferred to quantity restrictions (caps on emission), since the damages from climate change are relatively at. On the other hand, another recent piece of academic literature has highlighted the importance of adjusting carbon taxes to business cycle uctuations in a procyclical manner. In this paper, we analyze the optimal design and the relative performance of price versus quantity instruments in the face of uncertainty stemming from business cycles. Our theoretical framework is a general equilibrium real business cycle model with a climate change externality and distortionary scal policy. First, we nd that in an innitely exible control environment, the carbon tax uctuates very little and is approximately constant, whilst emissions uctuate a great deal in response to a productivity shock. Second, we nd that a xed price instrument is advantageous over a xed quantity instrument due to the cyclical behavior of abatement costs, which tend to increase during expansions and decline during economic downturns. Our results suggest that the carbon tax is approximately constant over business cycles due to \at" damages in the short-run and thus procyclical behavior as suggested by other studies cannot be justied merely on the grounds of targeting the climate externality.